Current treatments for biofilm‐associated periprosthetic joint infection and new potential strategies. Issue 7 (6th May 2022) - Visperas, Anabelle; Santana, Daniel; Klika, Alison K.; Higuera‐Rueda, Carlos A.; Piuzzi, Nicolas S.
Abstract: Periprosthetic joint infection (PJI) remains a devastating complication after total joint arthroplasty. Bacteria involved in these infections are notorious for adhering to foreign implanted surfaces and generating a biofilm matrix. These biofilms protect the bacteria from antibiotic treatment and the immune system making eradication difficult. Current treatment strategies including debridement, antibiotics, and implant retention, and one‐ and two‐stage revisions still present a relatively high overall failure rate. One of the main shortcomings that has been associated with this high failure rate is the lack of a robust approach to treating bacterial biofilm. Therefore, in this review, we will highlight new strategies that have the potential to combat PJI by targeting biofilm integrity, therefore giving antibiotics and the immune system access to the internal network of the biofilm structure. This combination antibiofilm/antibiotic therapy may be a new strategy for PJI treatment while promoting implant retention.